Vibration Analysis Of The Dam Physical Model Due To The Effect Of Water Spilling - Ganesan, Raguvaran (Universiti Sains Malaysia, 2019)
A dynamic characteristic of the dam structure is one of important criterion that need to be investigated regularly in order to monitor the reliability of the dam structure. Chenderoh dam located in Perak, Malaysia is one of the oldest dam and there is a requirement to study the dynamic characteristic of the dam. In this study, a 3D scaled dam model of the Chenderoh dam is constructed and modal analysis (MA) of the spillway section of the dam in terms of natural frequencies, mode shapes and frequency response function (FRF) are investigated using ANSYS software. Then, the operational deflection shapes (ODS) during the spilling of water through fluid structure interaction (FSI) study is investigated. The physical model is build to validated the result of MA and ODS between simulation and experiment. The result of the study is important for any disturbances induced from the vibration of the dam in the future.